Nitinol versus steel partially covered self-expandable metal stent for malignant distal biliary obstruction: a randomized trial - Soderlund, Claes; Linder, Stefan; Bergenzaun, Per E.; Grape, Tomas; Hakansson, Hans-Olof; Kilander, Anders; Lindell, Gert; Ljungman, Martin; Ohlin, Bo; Nielsen, Jorgen; Rudberg, Claes; Stotzer, Per-Ove; Svartholm, Erik; Toth, Ervin; Frozanpor, Farshad (Endoscopy, 2014)
Background and study aims: Covered nitinol alloy self-expandable metal stents (SEMSs) have been developed to overcome the shortcomings of steel SEMS in patients with malignant biliary obstruction. In a randomized, multicenter trial, we compared stent patency, patient survival, and adverse events in patients with partly covered stents made from steel or nitinol.Patients and methods: A total of 400 patients with unresectable distal malignant biliary obstruction were randomized at endoscopic retrograde cholangiopancreatography (ERCP) to insertion of a steel or nitinol partially covered SEMS, with 200 patients in each group. The primary outcome was confirmed stent failure during 300 days of follow-up. Results: At 300 days, the proportion of patients with patent stents was 77 % in the steel group, compared with 89 % in the nitinol group (P = 0.01). Confirmed stent failure occurred more often in the steel SEMS group compared with the nitinol SEMS group, in 30 versus 14 patients (P = 0.02). Stent migration occurred in 13 patients in the steel group and in 3 patients in the nitinol group (P = 0.01). Median patient survival (secondary outcome) was 137 days and 120 days in the steel SEMS and nitinol SEMS groups, respectively (P = 0.59).Conclusions: The nitinol SEMS showed longer patency time, and the nitinol group had fewer patients with stent failure, compared with the steel SEMS group. We could not detect any differences between the two groups regarding survival time, and regarding adverse event rate.Clinical trial registration : NCT 00980889